2015
DOI: 10.2486/indhealth.2014-0117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of higher frequency components and duration of vibration on bone tissue alterations in the rat-tail model

Abstract: To formulate more accurate guidelines for musculoskeletal disorders (MSD) linked to Hand-Arm Vibration Syndrome (HAVS), delineation of the response of bone tissue under different frequencies and duration of vibration needs elucidation. Rat-tails were vibrated at 125 Hz (9 rats) and 250 Hz (9 rats), at 49 m/s 2 , for 1D (6 rats), 5D (6 rats) and 20D (6 rats); D=days (4 h/d). Rats in the control group (6 rats for the vibration groups; 2 each for 1D, 5D, and 20D) were left in their cages, without being subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
1
2
0
2
Order By: Relevance
“…The results of a study by Peelukhana et al showed that the structural damage was significant for cortical bone while it remained insignificant for the trabecular bone. Furthermore, the results of this study showed that structural damage was significant at 5D time point for the cortical bone while the trabecular bone remained largely unaffected, with a change in trabecular spacing observed at 20D time point (23). Our results correlate with these data.…”
Section: Discussionsupporting
confidence: 85%
“…The results of a study by Peelukhana et al showed that the structural damage was significant for cortical bone while it remained insignificant for the trabecular bone. Furthermore, the results of this study showed that structural damage was significant at 5D time point for the cortical bone while the trabecular bone remained largely unaffected, with a change in trabecular spacing observed at 20D time point (23). Our results correlate with these data.…”
Section: Discussionsupporting
confidence: 85%
“…The physiological impact of vibration on the body is based on mechanical, physico-chemical and thermal (manifested to a lesser extent) effects. The expression of physiological mechanisms depends on intensity and parameters (frequency, amplitude) of impact, conditions of implementation and localization [3,4,6,7]. Frequencies in the range of 10-200 Hz have the most noticeable effect on body tissues.…”
Section: Results and Their Discussionmentioning
confidence: 99%
“…One of the physiotherapeutic methods of preventing contractures and restoring the mobility of joints after long-term immobilization is vibrotherapy (from Latin vibrare -to shake, oscillate and from Greek therapeia -treatment) [3,4]. The technique involves the influence of low-frequency mechanical waves, which is carried out in direct contact with the patient's tissues or body and leads to selective excitation by vibration of various mechanoreceptors, causing a number of physiological changes and sanogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Але цей інтерес полягав переважно у вивченні негативного впливу вібрації і пов'язаного з ним розвитку професійних захворювань. Десь наприкінці 80-х років оновився інтерес до низькочастотних механічних коливань уже щодо вивчення їх позитивного впливу на організм, у тому числі як терапевтичного методу лікування деяких ортопедичних захворювань [16,20]. З'явився новий термін -«вібротерапія».…”
Section: âñòóïunclassified
“…В основі фізіологічного впливу вібрації на організм лежать механічні, фізико-хімічні й теплові (які проявляються меншою мірою) ефекти. Вираженість відповідних фізіологічних механізмів залежить від інтенсивності й параметрів (частоти, амплітуди) впливу, умов проведення й локалізації [12,14,16,20].…”
Section: âñòóïunclassified